Pengaruh Health Education Terhadap Dukungan Psikososial Keluarga Dalam Merawat Pasien DM Tipe 2 - Cici Astuti; Masyita Haerianti; Irna Megawaty; Kurnia Harli; Irfan Wabula; Evidamayanti; Sahriana (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Type 2 diabetes mellitus is a chronic disease that requires family support for long-term care, particularly in psychosocial aspects. Family psychosocial support is crucial for improving patients’ motivation and quality of life. This study aims to determine the effect of health education on family psychosocial support in caring for patients with type 2 diabetes at the Ikram Wound Care Clinic. This study employed a quasi-experimental quantitative design using a non-randomized, without-control-group, pretest-posttest approach. The study population consisted of all families of Type 2 DM patients receiving care at Ikram Wound Care Clinic, with a total sample of 31 respondents in June–July 2025. The instrument used measured family psychosocial support in caring for patients with type 2 diabetes. The results of the Marginal Homogenity test analysis showed a p<0.001, leading to the rejection of H0, which indicates a significant effect. Thus, the study concluded that there is a significant effect of health education implementation on family psychosocial support in caring for patients with type 2 diabetes at Ikram Wound Care Clinic. Psychosocial support is essential for families caring for patients with type 2 diabetes, as a decline in the quality of family support significantly impacts the patient’s quality of life.